CRIMINAL LAW CHALLENGES CAUSED BY MIGRATION FOR WORK - Iancu, Elena-Ana (International Journal of Legal and Social Order, 2025)
In the first part of the study, we make reference to migration theories that are enshrined in scientific research, because we consider that a better comprehension of the context in which people choose and decide to migrate (emigrate-immigrate) would bring solidarity to the forefront. We also emphasise the importance of the existence of an appropriate legal framework where public safety, national security and legal security can be ensured. Knowing the forms of communication in intra-institutional and inter-institutional relations and when we are available to investigate our inner selves to find the resources required in order to act on a daily basis to increase the good around us as long as, on a social-professional level, we are pleased with our accomplishments, is also important so that we can avoid manipulation by various means. We will manage to be active in the line of preventing criminal offenses, of detecting acts of violence committed in different environments and sometimes, if we are part of certain structures or entities, we will also be involved in complex processes aimed at combating crimes, maintaining appropriate social dialogue, as well as constitutional order and social order. In the final part of the article, we will present a few challenges raised by migration, with reference to legal rules of criminal law, labour law or included in the special law with legal provisions on preventing and combating domestic violence. Being aware of influence factors such as: race, language, religion, nationality, financial status, level of education and type of skills held, is an important aspect, knowing that social micro-groups change in the context of migration (emigration-immigration).